Technology Use in Elementary Music Education: A Scoping Review - David T Casali (Journal of the Association for Technology in Music Instruction, 2025)
The purpose of this scoping review was to look at how music technology has been used in the elementary music classroom from 2020 to April 2025. Uses of technology were organized using the Substitution, Augmentation, Modification, and Redefinition (SAMR) model (Puentedura, 2006). Only articles that both described how technology was used and what the learning process looked like were included. A total of 26 articles met the criteria for inclusion. Multiple uses of technology across the four levels of the SAMR were represented from 14 different countries. An article from each of the four SAMR levels is described in depth to elucidate how uses of technology were categorized. Many cases of researcher-designed technology were found, especially at the redefinition level of the SAMR model, that provided students with transformative music making experiences such as exploring synthesizers using eye tracking, exploring an augmented reality musical pop-up book, and engaging in collaborative composition using iconic notation. I identified gaps in the literature, including the paucity of articles involving students with disabilities, preschool students, artificial intelligence, and phenomenological research methods.
Keywords: Music technology; elementary music; technological tools; technology; music software; music education